Strategies for Strengthening Digital Islamic Religious Education in Overcoming Religious Disinformation - Hidayatulah, Ahmad Syarif; Sholikah, Mar’atus; Hadi, Imam Anas; Nugroho, Wahyu; Yusuf, Muhamad Hani (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the role of Islamic Religious Education (IRE) in addressing religious disinformation in the digital era. Advances in information technology have introduced new challenges, such as the spread of negative content and the potential for radicalism, largely due to low digital literacy and a lack of ethical awareness in social media use among young people. Using a literature review method, this research analyzes various sources to identify the challenges, opportunities, and strategies for integrating IRE with digital technology. The findings highlight the urgency of digital and religious literacy to equip students with the ability to distinguish between accurate and misleading information. Key strategies include integrating digital literacy into the IRE curriculum, strengthening the role of teachers as agents of religious moderation, implementing contextual and critical learning, fostering digital ethics, and promoting collaboration among schools, parents, and online communities. The study recommends developing an adaptive IRE curriculum, enhancing teacher competence, and utilizing technology to cultivate a generation of Muslims who are religiously grounded, critical, moderate, and resilient in the face of digital disinformation.